Kazakh perspective on China, the Chinese, and Chinese migration - Burkhanov, Aziz; Chen, Yu-Wen (Ethnic and racial studies, 2016)
Discourse analysis of different languages of newspapers in Kazakhstan reveals that Kazakhstanis' views towards China and the Chinese are divided. The official discourse in both state-sponsored Russian and Kazakh newspapers is in accordance with the country's policy towards further engagement with their rising Chinese neighbour. However, negative stereotypes of China and the Chinese, as well as sinophobia, are pervasive in private Kazakh language newspapers. Private Russian newspapers have a more nuanced view towards China, with a hidden inclination towards being critical of that country and its people. Although the majority of these societal voices do not have a direct impact on changing the national policies of Kazakhstan, they are important in the sense that Kazakhstan's ruling elite must continue to gauge social views and to placate differences in order to secure the stability and legitimacy of the regime.